Descriptive epidemiology of brain and central nervous system cancers in Central and South America. (September 2016) - Piñeros, Marion; Sierra, Mónica S.; Izarzugaza, M. Isabel; Forman, David
Highlights: Brazil, Uruguay, Colombia and Cuba have highest brain and CNS cancer incidence rates in both sexes, reaching rates of intermediate level. Males have 10–50% higher brain and CNS cancer incidence and mortality rates than females. Differences in incidence rates among countries could be due to underreporting and under ascertainment of cases. Gliomas are the most frequently diagnosed brain and CNS cancers in the region. The percentage of unspecified malignant tumors of brain and CNS is remarkably high (33%) in Central and South America. Abstract: Rationale and objective: Although malignant tumors of the brain and central nervous system (CNS) represent less than 3% of new cancer cases estimated worldwide, they cause significant morbidity and in the case of gliomas, the most common histological type, have a poor prognosis. We describe patterns and trends in brain and CNS incidence and mortality in Central and South America. Methods: We obtained regional- and national-level incidence data from 48 population-based cancer registries in 13 countries and cancer deaths from the WHO mortality database for 18 countries. We estimated world population age-standardized incidence rates (ASRs) and mortality rates (ASMRs) per 100, 000 person-years, and present incidence by histological subtypes. Results: In general, incidence rates were higher in males than in females. The highest incidence ASRs were observed for Cuba (5.1 males, 3.6 females) in Central America, and for Brazil (6.4 males, 4.8 females) and Uruguay (6.2 and 4.0) in South America. Mortality rates closely followed the pattern of incidence rates. Argentina, Brazil and Chile showed increasing mortality trends, although these were not statistically significant. Glioma and unspecified tumors were the most common histological types, accounting for 55.4% and 32.8%, respectively. The proportion of microscopically verified diagnoses was 47–70% in most countries. Conclusion: Although incidence and mortality rates in general were low, some countries displayed high- to intermediate-level incidence rates; under-reporting and under-ascertainment of cases could contribute to the geographic variations observed. There is a need to improve both the ascertainment of cases and the accuracy of histological diagnosis. Monitoring of brain and CNS cancers along with etiological research remain priorities.